Metal Oxide Oxidation Catalysts as Scaffolds for Perovskite Solar Cells - Peter Holliman (Materials, 2020)
Whilst the highest power conversion efficiency (PCE) perovskite solar cell (PSC) devices that have reported to date have been fabricated by high temperature sintering (>500 °C) of mesoporous metal oxide scaffolds, lower temperature processing is desirable for increasing the range of substrates available and also decrease the energy requirements during device manufacture. In this work, titanium dioxide (TiO2) mesoporous scaffolds have been compared with metal oxide oxidation catalysts: cerium dioxide (CeO2) and manganese dioxide (MnO2). For MnO2, to the best of our knowledge, this is the first time a low energy band gap metal oxide has been used as a scaffold in the PSC devices. Thermal gravimetric analysis (TGA) shows that organic binder removal is completed at temperatures of 350 °C and 275 °C for CeO2 and MnO2, respectively. By comparison, the binder removal from TiO2 pastes requires temperatures >500 °C. CH3NH3PbBr3 PSC devices that were fabricated while using MnO2 pastes sintered at 550 °C show slightly improved PCE (η = 3.9%) versus mesoporous TiO2 devices (η = 3.8%) as a result of increased open circuit voltage (Voc). However, the resultant PSC devices showed no efficiency despite apparently complete binder removal during lower temperature (325 °C) sintering using CeO2 or MnO2 pastes.